IDENTIFIKASI SENYAWA KIMIA PADA BUAH SEGAR TERUNG POKAK (Solanum torvum) DENGAN METODE LCMS - Nunuk Helilusiatiningsih (Journal of Food Technology and Agroindustry, 2021)
The content of antioxidant compounds in pokak eggplant (Solanum torvum) had the potential as an herbal medicine and was consumed by the world population. The research objective was to study the chemical compound content of the LCMS method. Experimental design with fresh fruit extraction of pokak eggplant using 95% ethanol solvent. The parameters measured were the chemical components found in fresh fruit. The results of analysis of chemical compounds include Choline, Proline, Bis (2-ethylhexyl) phthalate, BMK ethyl glycidate, 4- Methoxycinnamic acid, chlorogenic acid, 7- Hydroxycoumarine, Trigonelline, 1- Vinylimidazole, Pipecolic acid, L- (+) - Arginine- Stearoylglycerol, Caffeine, Cetrimonium, l- Pyroglutamic acid, Erucamide, Muscone, Cucurmin, Stearamide, Betulin, Acetophenone, Ethyl oleate, SSR146977, D - (+) - Maltose, M-144, Monoolein, L-ide, Histidine, Tomatidine, Oleamide Hexadecanamide, Isoleucine, DIPEA, L- Aspartic acid, Octadecanimine, Maltol, 1-Linoleoyl glycerol, 3- Hydroxy-L- proline, Sakuranin, Leucylprolin, Diaminopimelic acid, Nervonic acid, Nootkatone, Caffeic acid, 5-Hydroxymethyl , Methyl cinnamate, Octyl decyl phthalate, 1-Aminocyclohexanecarboxylic acid, Glycerophospho-N-palmitoyl ethanolamine, 4-Methoxybenzaldehyde, Methyl palmitate, Cyclohexyl, phenyl ketone, Esculin, n-Pentyl isopentyl phthalate, - 6 -Ketoprostaglandin F1α, N, N-Dimethylsphingosin e, α-Eleostearic acid, cis-12-Octadecenoic acid methyl ester, Oleoyl ethanolamide, Citral, L-Tyrosine, XLR-11, Isovanillic acid, 1-Tetradecylamine, Isoquinoline, Calocarpin, Sedanolide, N-Acetyltyramine, Testosterone isocaproate , 2-Methyl-S-benzothiazole, 1-Aminocyclohexanecarboxylic acid, 4-Methylumbelliferyl-α-D-glucopyranoside, Dodecyltrimethylammonium, cis, cis-Muconic acid, 6-Ketoprostaglandin 4-octopamine, Lupeol, N-FeroyETl, [4- (4-Hydroxy-3-methoxyphenyl) tetrahydro-1H, 3H-furo [3,4-c] furan-1-yl] -2-methoxyphenyl hexopyranoside.